Ethical Use of Information Technology in Higher Education - LeBeau, Stephen (Journal of Interdisciplinary Studies in Education, 2022)
With the use of technology continuing to increase in higher education, Liliana Mâţa has met the need for knowledge on the ethics of information technology. Ethical Use of Information Technology in Higher Education specially looks at the ethical questions that technology has brought to colleges and universities since the 1980s. This book looks at both ethical problems and solutions relating to the use of information technology across higher education with the goal of identifying and increasing awareness for the ethical issues technology brings to education activities.